Strategies and nuances in English-Chinese poetry translation: a decadal review - Yuqing, Chen; Chwee Fang, Ng; Zainal, Zainor Izat (AWEJ Publishing, 2024)
When translating poetry, the unique literary genre poses a significant challenge to the translator's ability. The work of translating English poems into Chinese has a history of 20 years in China. In this paper, the author collected and studied the strategies used in the translation of English poetry into Chinese from 2014 to 2024, focusing on solving the persistent confusion surrounding key terms such as “translation strategy”, “translation method” and “translation technique”. This study aims to clarify these structures and examine their practical significance in the context of real translation. In the decision-making process of translation strategy selection, translators need to balance cultural and aesthetic expectations with the practical application of these strategies. In this paper, a systematic literature review method is adopted as the methodology, and the results emphasize the importance of balancing domestication and foreignization strategies to ensure translation fidelity and emotional resonance. In addition, the study summarizes seven key research gaps, including the need for more empirical research to verify the effectiveness of these strategies in different contexts. This paper emphasizes the value of continuous academic discussion in improving translation practice, respecting both the original text and the nuances of regional languages, thereby contributing to a richer and more effective exchange of Chinese-English literature.